The Effects of ESG on Firm Value with Profitability as a Moderation Variable in Sensitive and Non-Sensitive Industries - Moh Saiful Hakiki; Tatang Ary Gumanti; Tasrim Tasrim; Martino Wibowo (Jurnal Ilmiah Manajemen Kesatuan, 2026)
The increasing importance of ESG in corporate strategy and investment decisions, combined with mixed empirical evidence and limited context-specific studies in developing countries like Indonesia, is a concern. The study aims to explore whether ESG disclosure has different short-term and long-term effects and whether profitability moderates the ESG and firm value causality relationship. The study employs panel data regression across four models to examine short- and long-term effects in sensitive and non-sensitive industries. The findings indicate that ESG components do not have consistent direct effects on firm value across industries and time horizons, with only limited evidence of a negative impact of governance in the long-term non-sensitive industry. However, profitability plays a significant moderating role, particularly in non-sensitive industries, where environmental and social interactions become significant in the long term, and social in the short term. In sensitive industries, only governance shows a significant moderating effect in the short term, while no individual moderating effects persist in the long term despite joint model significance. These findings imply that ESG strategies should be implemented in alignment with firm profitability and industry context, as their value relevance emerges primarily through interaction effects rather than as standalone factors.